PATRIOTISM AND LOVE IN THE POETRY OF ABDULLA ARIPOV: SPIRITUAL VALUES AND NATIONAL IDENTITY - Gofurova Jayrona Bekhzodovna (Bright Mind Publishing, 2025)
This article examines the work of the renowned Uzbek poet Abdulla Aripov through the lens of two central themes — patriotism and love. The author focuses on how the poet expresses his devotion to the Motherland, national values, language, and people in his poetry. Special attention is given to poems such as "The Motherland", "You Are Not an Orphan", and "My Native Language", which vividly convey deep respect, loyalty, and a spiritual bond with the native land. It is emphasized that Aripov’s patriotism is not limited to slogans but is presented as a philosophical and moral concept closely linked to the notion of love. Love in Aripov’s poetry is multifaceted: it encompasses love for one’s mother, language, history, and national culture. The article highlights the significance of Aripov’s poetry in educating the younger generation, fostering a sense of national identity, and shaping spiritual values. His creative legacy serves as a powerful source of inspiration, instilling respect for one’s roots and awakening a deep sense of responsibility for the fate of the homeland.
Keywords: Abdulla Aripov, patriotism, love, Motherland, poetry, national values, Uzbek literature, native language, culture, spirituality.